The Relationship Between Fruit and Vegetable Consumption and Nutritional Status in Adults - Andi Nursiah; Cakrawati R Cakrawati R (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Background : Adequate consumption of vegetables and fruits is an important component of a healthy diet. Low consumption May be associated with inadequate fiber and micronutrient intake and an increased risk of nutritional problems . WHO recommends adults consume at at least 400 grams of vegetables and fruits per day . Objective : This study aimed to determine the relationship between vegetables and fruit consumption and nutritional status among adults . Methods : This quantitative analytical study used a cross-sectional design . The sample consisted of 92 adults selected using purposive sampling. Vegetable and fruit consumption was assessed using a structured food frequency questionnaire , while nutritional status was determined based on body mass index . Data were analyzed using the Chi- Square test with a significance level of 0.05. Results : Of of the 92 respondents , 38 (41.3%) had adequate vegetables and fruit consumption , while 54 (58.7%) were inadequate consumption . A total of 59 respondents (64.1%) had normal nutritional status, 21 (22.8%) were overweight , and 12 (13.1%) were obese . Statistics analysis showed a significant relationship between vegetables and fruit consumption and nutritional status (p=0.021). Conclusion : Vegetable and fruit consumption was significantly associated with nutritional status among adults . Increasing vegetables and fruit consumption as part of a balanced diet may contribute to maintenance healthy nutritional status.